Kelarutan kalsiumemail pada saliva penderita tuna netra (Dissolution of enamel calcium in saliva of patients with visual impairment) - Hendri Jaya Permana; Didin Erma Indahyani; Yenny Yustisia (DiscoverSys Inc., 2014)
Patients with visual impairment experienced debris, calculus and a high index of oral hygiene. Low salivary flow anddifficulty in cleaning the oral cavity in patients with visual impairment caused high accumulation of plaque that causesa decrease in the pH of saliva. Low pH of saliva affects the balance of the composition of inorganic email. Calcium isthe largest inorganic content of the email, thus dissolving calcium email can be an indication of enameldemineralization. This study aimed to determine the solubility of calcium in saliva of blind patients, and salivary pHrelationship with the solubility of calcium. This experimental laboratory study used saliva taken from 8 blind patientsand artificial saliva as a medium of enamel pieces soaking for 24 hours. Dissolved calcium levels were measured byatomic absorption spectrophotometer. The results showed that the solubility of calcium in the saliva of blind patientsgreater than the control group (p<0.05). Pearson correlation test demonstrate the relationship between salivary pHand solubility of calcium enamel, so the lower the pH the greater enamel calcium dissolution. It was concluded that themagnitude of the solubility of calcium enamel due to decreased of salivary pH.